Simultaneous central and peripheral nervous system involvement inthe same patient: An interesting case report - Sharma, Tarun; Jain, Prachi; Chander, Subhash; Aswal, Rohit; Sethi, Monalisa; sharma, Aradhna (Indian Journal of Case Reports, 2026)
Involvement of the central and peripheral nervous systems (PNS) in the same patient is a rare phenomenon. The causes can be clubbed as infective, demyelinating diseases like multiple sclerosis, or may be post-vaccination. Neurotoxins are also associated with demyelination. Either of the two may present earlier, followed by the other one. Due to the involvement of both central and peripheral, the patient usually becomes moribund much earlier. If not diagnosed earlier, the patient may have difficulty surviving. Here, we present an interesting case in which both the central and PNSs were involved in the same patient. The cause we found out was infectious, and the patient improved with therapy and has been under follow-up for the last 3 months on treatment. The case in itself is very essential for primary care physicians, as non-specific multiple neurological symptoms, if diagnosed early, may benefit the patient.